Contribuição ao estudo da pneumonia de aspiração em idosos submetidos à avaliação videofluoroscópica da deglutição - Carla Maria Correa Tanure (2008)
Brazil's geriatric population growth occurs at large rates. Around 32 million people over 60 years old are expected within the next 15 years, which means an increase of chronical disabling diseases that can generate complications associated to oropharyngeal dysphagia. The tendency is that morbidity increased by oropharyngeal dysphagia will amplificate the prevalence of aspiration pneumonia which leads to worsening the elderly population's health situation and also interfering in their quality of life and health costs. The purpose of this study was to investigate the correlation between dysphagia severity and the risk of the elderly population developing aspiration pneumonia with associated diseases under videofluoroscopic vision of deglutition. Videofluoroscopic views of 217 elderly were analyzed, divided in five groups according to: normal deglutition, slight oral phase alteration without aspiration, laryngeal penetration, tracheal aspiration and silent aspiration. To determine pneumonia occurrence, clinical and radiological data was investigated in the time span of six months prior and after deglutition videofluoroscopic execution. The variables included in breathing and clinical data analysis were age, sex, original disease, feeding way, coughing, fever, prostration, oxygenotherapy use and radiological image compatible with pneumonia. The analysis of the results revealed that 106 individuals with average age of 82 evolved with aspiration pneumonia, with statistical difference (p value = 0.000) when compared with the group without pneumonia. The main risk factor was central neuropathy with prevalence of 72.5%. Videofluoroscopy revealed that pneumonia was observed in two patients (0.9%) with normal deglutition, 15 (6.9%) with slight deglutition alteration, 16 (7.4%) with laryngeal penetration, 22 (10.1%) with tracheal aspiration and 51 (23.5%) with silent aspiration. Elderly with tracheal aspiration and silent aspiration had 170 and 280 times, respectively, more chances to develop aspiration pneumonia. The existence of correlation between aspiration pneumonia development and dysphagia severity observed by videofluoroscopy was verified.